2017
DOI: 10.1177/1747954117742652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coaching behaviors on job satisfaction and organizational commitment: The case of comprehensive community sport clubs in Japan

Abstract: Coaches are widely regarded as playing an important role in the development of comprehensive community sport clubs, in terms of meeting the needs of club members and club staff. However, few studies have explored the coaching activities of comprehensive community sport clubs in Japan. This study, therefore, aimed to examine the effect of coaching behaviors in comprehensive community sport clubs on job satisfaction and organizational commitment. One hundred seventy-seven coaches completed questionnaires assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Autonomy is in the nature of coaching, it is a prerequisite for a coach to train, lead, inspire. This result is in line with Takamatsu's and Yamaguchi's (2018) results in a similar study, where they argue that autonomy is a necessary precondition for increasing coaches' job satisfaction and organizational commitment. Additionally, the results of this study showed the lowest correlation among job satisfaction dimensions between 'coaching job' and 'amount of work'.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Autonomy is in the nature of coaching, it is a prerequisite for a coach to train, lead, inspire. This result is in line with Takamatsu's and Yamaguchi's (2018) results in a similar study, where they argue that autonomy is a necessary precondition for increasing coaches' job satisfaction and organizational commitment. Additionally, the results of this study showed the lowest correlation among job satisfaction dimensions between 'coaching job' and 'amount of work'.…”
Section: Discussionsupporting
confidence: 91%
“…Many researchers agree that the relationship with colleagues is one of the major sources of job satisfaction (Drakou, 2006;Rintaugu, 2013;Takamatsu & Yamaguchi, 2018). Regarding this study satisfaction with the relationship with colleagues was among the three highly scored dimensions together with satisfaction with autonomy and coaching itself.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Some important aspects and characteristics considered in this model should be noted: (1) a strong belief and acceptance of the aims and values of the organization; (2) a will to exercise considerable effort in the name of the organization; and (3) a defined wish to continue being a member of the organization so that affective adherence is emphasized (Mowday et al , 1979). As we have said before, other empirical studies use the one-dimensional model of organizational commitment as their reference (among others, Darwish, 2003; Ke and Deng, 2018; Takamatsu and Yamaguchi, 2018; Shahid and Zain, 2018) because it has suitable characteristics that are applicable in the business reality of economic globalization. From this point of view, the commitment would only really have an aspect related to the emotional and affective attachment to the organization someone works in.…”
Section: Literature Reviewmentioning
confidence: 99%